COMPARATIVE STUDY OF THE FLEXURAL STRENGTH OF MAXILLARY DENTURE BASES MADE IN CONVENTIONAL AND HIGH IMPACT HEAT CURE ACRYLIC RESIN - Sadia Akram; . Fahimullah; Nuzhat Ayub; Amjad Hanif; Zudia Riaz; Beenish Haider (Khyber Medical University Journal, 2022)
OBJECTIVE: To compare the flexural strength of maxillary denture bases made in high impact and conventional heat cure acrylic resin. METHODS: This experimental laboratory-based study was conducted in Peshawar Dental College, Materials Research and Centralized Resource Laboratories University of Peshawar, Pakistan. Total 120 edentulous maxillary casts, sixty each of conventional acrylic (30 in subgroup-IA for shallow palate and 30 in subgroup-IB for deep palate and high impact acrylic (30 in subgroup II-A for shallow palate and 30 in subgroup II-B for deep palate) were made. These were then tested for ﬂexural strength using universal testing machine. The load was applied at the rate of 5.0 mm/min. Independent samples t-test was applied for statistical analysis. RESULTS: Mean values of deflection at fracture, fracture load and flexure strength were 0.309±0.059 cm, 87.729±22.497 Kg and 13.645± 4.453 kg/cm² respectively. Mean Flexure Strength (kg/cm2) was 8.30±1.27, 16.54±1.77, 10.88±1.01 and 18.85±1 in subgroups I-A, I-B, II-A and II-B respectively (<0.001). Mean deflection at fracture (cm) was 0.24±0.04, 0.29±0.03, 0.35±0.03 & 0.368±0.03 in subgroups I-A, I-B, II-A and II-B respectively (<0.001).Mean Fracture Load (Kg) was 69.97±3.12, 114.9±6.75, 63.28±7.05 & 102.8±5.5 in in subgroups I-A, I-B, II-A and II-B respectively (<0.001). CONCLUSION: High impact acrylic resin was found to have significantly higher flexure strength as compared to conventional acrylic resin